2023
DOI: 10.1007/s10578-023-01535-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Autism Spectrum Disorders - Validation of the Portuguese Version of the Social Communication Questionnaire

Abstract: There are no assessment and screening tools for Autism Spectrum Disorders (ASD) validated for the Portuguese population. The Social Communication Questionnaire (SCQ) is an useful screening tool of ASD diagnosis. The main objectives of our study were to produce a Portuguese version of the SCQ (SCQ-PF), study its internal consistency, sensitivity and specificity in order to evaluate its validity as a screening instrument for ASD. We also wanted to study the impact of intellectual disability and verbal impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In accordance with other international studies, parents in our study first noticed delays in social development, followed by ritualistic behaviours and behavioural problems. While these symptoms represent the triad of impairments characteristics of ASD, they are also more likely to be observed later in children’s development (Araújo et al , 2023; Pereira et al , 2018), which corroborating our results of a later age of first concern. However, given that Portuguese parents noticed difficulties in their child’s development at a later age, indicating that knowledge of early behavioural milestones and markers of ASD are essential for parents to hasten the diagnosis process.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In accordance with other international studies, parents in our study first noticed delays in social development, followed by ritualistic behaviours and behavioural problems. While these symptoms represent the triad of impairments characteristics of ASD, they are also more likely to be observed later in children’s development (Araújo et al , 2023; Pereira et al , 2018), which corroborating our results of a later age of first concern. However, given that Portuguese parents noticed difficulties in their child’s development at a later age, indicating that knowledge of early behavioural milestones and markers of ASD are essential for parents to hasten the diagnosis process.…”
Section: Discussionsupporting
confidence: 89%
“…However, the present results indicated an increase in the mean age of formal diagnosis compared to the study realized by Salomone et al (2015) that found the mean age to be 2.79 years. A possible explanation for this potential delay may be the characteristics of symptom severity in our sample and the inefficiency of the diagnostic practices in the last 15 years (Araújo et al , 2023). In addition, we found that on average parents consulted 3.62 professionals (ranging one to eight professionals) of various fields of expertise before obtaining the formal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations